Development of low coefficient of thermal expansion composite substrate for electronic packaging using finite element method - Pang, Hooi San (2007)
Coefficient of thermal expansion (CTE) mismatch between the different material layers in the substrate leads to residual warpage and stresses. Such deformation adds additional mechanical constraints to solder joint attached on the surface of substrate and subsequently leads to solder joint reliability issue of the electronic package. Thus, a new composite material was evaluated with the aim to reduce both in-plane and out-of-plane CTE of the core substrate. In this study, equivalent thermo-mechanical and viscoelastic properties of silica-filled epoxy were predicted with finite element method. The silica-filled epoxy was served as the matrix of the core substrate and woven glass were embedded as few layers in the matrix phase. Viscoelastic response of the matrix phase and resulting orthotropic of the multilayered substrate were modeled. Substrate warps in concave shape after subjected to curing temperature due to CTE mismatch and asymmetry of geometry. For surface mount assembly, accumulated inelastic strain in the critical solder joint with low CTE composite substrate is lower than that of with conventional FR-4 substrate during the solder reflow and temperature cycles. In addition, the predicted life cycle of the low CTE composite assembly is 36.9 % longer compared to assembly with FR-4 substrate.